Calculation of sound power level of tandem axial fan - Doroshenko, Ekaterina; Tereshchenko, Yuriy; Lastivka, Ivan; Tereshchenko, Yuriy (Eastern-European Journal of Enterprise Technologies, 2017)
A numerical simulation of the flow in axial fans with single and tandem geometrically equivalent blade rows was carried out. During the research, the sound power level of the fans was calculated. The acoustic characteristics of the single fan obtained in the numerical experiment were compared with the results of the physical experiment. The divergence between the results of the physical and numerical experiments on the sound power level for the first harmonic is 0.08 %, for the second harmonic – 0.35 %. In order to reduce the acoustic emission, a 3D model of the axial fan with the geometrically equivalent tandem row was constructed. The results showed that at the fan rotation frequency of 900 rpm, the sound power level on the first two harmonics is reduced by more than 7 dB. Also, the change in the total sound power level for axial single and tandem fans in the rotation frequency range of 900 to 1,500 rpm was investigated. The fan with the geometrically equivalent tandem blade row has the total sound power level by 6.9...7.4 dB lower than the single fan. The use of the tandem axial fan allows improving acoustic characteristics